Treating Renal Pelvic Stones with Rigid Ureterorenoscopy (Annals of Medical Research, 2021)
Aim: To evaluate the treatment of renal pelvic stones with rigid ureterorenoscopy.
Keywords: Rjid Ureterorenoscopy; Renal Pelvic Stone; Treatment.